Modification of Coal Fly Ash Waste into Manganese-Oxide-Coated-Zeolite (MOCZ) to Adsorb Heavy Metal Ions Ni2+ - Saputro, Sulistyo; Mahardiani, Lina; Susilowati, Endang; Nurhayati, Nanik Dwi; Ciptonugroho, Wirawan; Windiasty, Ananda Dea; Prihantoro, Alita Selvi (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
High consumption of coal as a source of electrical energy in Indonesia has resulted in piles of waste from coal burning, namely fly ash, which can damage the environment and harm health. Fly ash contains main oxides, namely silica (SiO2) and alumina (Al2O3), whose components are similar to zeolite, so they can be synthesized into zeolite-like material (ZLM) which can be used as an adsorbent for heavy metal Ni2+. Therefore, this research discussed the characterization of manganese-oxide-coated-zeolite (MOCZ) from fly ash waste as a heavy metal adsorbent. The research procedure consisted of preparation, purification, and activation stage of fly ash to obtain fly ash that is free from impurities, the stage of making sodium silicate and sodium aluminate, and zeolite synthesis. The resulting zeolite was then coated with manganese oxide to expand the surface area of the zeolite and increase the ability of zeolite to adsorb heavy metal Ni2+. The research results showed that fly ash waste that was coated with manganese oxide can adsorb heavy metal Ni2+. The adsorption of the Ni2+ metal ion solution by zeolite with MOCZ modification is in line with the pseudo-second-order kinetic and Langmuir isotherm.